Analysis and establishment hierarchy of the values of the students of formative cycle of average-high degree (training formation) through a process of analytical triangulation - Rodríguez-Sabiote, Clemente; Álvarez Rodríguez, José; López Núñez, Juan Antonio; Campos Soto, María Natalia (Revista Complutense de Educación, 2018)
The objective of this study was to determine the importance that the students of the training cycle of Middle-Higher Degree of the province of Granada (Spain), grants to a set of values. A validation hierarchy has been established through an analytical triangulation process. The most relevant conclusión of the study is the establishment of a hierarchy distributed in four groups: in the first one, of very high relevance, there are items that denote values such as: affectivity, empathy, happiness and creativity. In the second group, of high relevance, values such as motivation, healthy eating, physical exercise, environment, value, choice, conflict resolution, family, etc. stand out. The third group, of moderate importance, is made up of items that allude to: changing jobs, getting carried away by instincts, getting good grades, democracy, being Spanish, politics, diversity of religions, etc. The last group, of low relevance, is related to values such as the deterioration of the environment and the prospective of the future.
Keywords: values; vocational training; analytical triangulation; axiological hierarchization